2021
DOI: 10.1038/s41598-021-94157-w
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic weighting of restrained subjects during exhaustion recovery causes loss of lung reserve volume in a model of police arrest

Abstract: Restraint asphyxia has been proposed as a mechanism for some arrest-related deaths that occur during or shortly after a suspect is taken into custody. Our analysis of the literature found that prone positioning, weight applied to the back, recovery after simulated pursuit, and restraint position have led to restrictive, but non life-threatening respiratory changes when tested in subsets. However, the combined effects of all four parameters have not been tested together in a single study. We hypothesized that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Prolongation of this situation will result in continued carbon dioxide accumulation. Campbell has demonstrated that prone positioning results in increased work of breathing [88]. Moreover, hyperventilation requires substantial work, with the work of breathing increasing geometrically with the need.…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of this situation will result in continued carbon dioxide accumulation. Campbell has demonstrated that prone positioning results in increased work of breathing [88]. Moreover, hyperventilation requires substantial work, with the work of breathing increasing geometrically with the need.…”
Section: Discussionmentioning
confidence: 99%